Institutional Transformation of Ex-PNPM-MPd UPK as A Revolving Fund Institution in Candipuro District, Lumajang Regency - Hadi Sulistyo; V. Rudy Handoko (Journal of Innovation and Applied Technology, 2020)
The termination of PNPM Mandiri Perdesaan (PNPM-MPd) in 2015 required UPK of Candipuro District as a revolving fund institution to transform to obtain legal certainty. This study aimed to describe the transformation of revolving fund management in Candipuro UPK, Lumajang Regency. This study used a descriptive qualitative method to examine institutional transformation based on aspects of legality, institutional (organizational management), philosophy, finance, and business form